Protection of cultural property in crisis conditions in the City of Zagreb - Cerjan, Marko; Ilijaš, Ozren; Bonc, Suzana (Crisis Management Days, 2025)
Abstract: Cultural goods are tangible and intangible goods; movable and immovable property of cultural-historical, artistic, architectural, paleontological, archaeological, ethnographic, anthropological and scientific significance; intangible forms and phenomena of man's spiritual creativity in the past that are of interest to the Republic of Croatia and are entered into the Register of Cultural Goods of the Republic of Croatia on the basis of the Decision on the Proclamation of the Status of Cultural Property. Movable cultural property can be all objects and records of cultural, historical, artistic, paleontological, archaeological, anthropological, ethnological, scientific, technical and social significance: individual objects and collections in museums, libraries, archives and other institutions; individual objects, collections, sacral inventories and equipment owned by religious communities; movable archaeological finds and objects and collections of other legal and natural persons. Immovable cultural heritage with the established property of cultural property consists of individual buildings and/or complexes of buildings, cultural and historical units and landscapes. Immovable cultural property represents architectural heritage from an individual building to a whole (group of buildings) or area (landscape). The paper will analyze on the example of the City of Zagreb what needs to be considered in order to optimally and responsibly approach the protection of cultural property in crisis conditions, what are the differences in treatment depending on the manifestations of threats, threats will be categorized according to the time of action/preparation for the protection of the property, and an assessment of the risk of total destruction of the property will be made with regard to the type of threat and the type of cultural property with the intention that the proposed assessment model can be applied in the analysis of the risk of total destruction of each object of immovable cultural heritage (e.g. building, church, palace, monument) and specific sets of movable cultural property. This can help in planning the prioritization of investments in the protection of cultural property. The paper will also present examples of good practice, but also present proposals with the purpose of further improving the level of protection. 1. INTRODUCTION During major accidents and catastrophes, all segments of the human community are destroyed. One of them is cultural property, which is an indispensable proof of cultural creation and upgrading over the centuries. Cultural property is by its very nature endangered and must be treated with special care, since due to their age they are sensitive to weathering and structurally impervious to threats such as earthquakes. Measures for the protection and preservation of movable cultural property are strict and prescribed in detail, and all cultural institutions adhere to them under normal circumstances. However, the problem arises during emergencies such as major accidents and disasters when they cannot be protected in the usual way because there is not enough time or conditions. In such situations, it is necessary to save and preserve as much as possible with as few necessary resources as possible. In order to achieve this, it is necessary to make an assessment of the risk of total destruction of the property with regard to the type of threat and the type of cultural property at the level of the institution that preserves and stores the cultural property, in order to create the preconditions for planning the course of action with the aim of urgent protection during major accidents and disasters. While it is possible to evacuate and relocate movable cultural property, and therefore planning is required at the micro level (at the level of the institutions that own the cultural property), immovable cultural property can only be protected by taking preventive measures, mainly related to the strengthening of the structures themselves, because neither relocation nor evacuation is possible. Therefore, with the aim of protecting immovable cultural property, it is also necessary to make a risk assessment not only with regard to the manifestation of possible threats, but also with regard to value and significance, in order to prioritize cultural heritage at the state level in a situation of always insufficient financial resources for the restoration and anti-seismic strengthening of the entire immovable cultural heritage. 2. METHODOLOGY The main methods used in the paper are analysis, categorization and evaluation. The analysis provides knowledge of all threats that can lead to the total destruction of cultural property with regard to the type and characteristic of the cultural property, the categorization groups certain specifics into logical groups according to common properties, while the assessment ranks the consequences of events that can lead to the destruction of cultural property. 3. RESULTS In order to optimally approach the protection of cultural property, we must first detect what threatens them and in what way, and plan protection measures accordingly. Threats do not manifest themselves in the same way given the time we have to prepare for the occurrence of an event and the type of measures that can be taken with the aim of protecting cultural property. For this reason, the paper lists sources for the assessment of internal and external threats, guidelines for categorization/selection of materials, and an assessment of the risk of total destruction of materials with regard to the type of threat and the type of cultural property. The aim of this paper is to point out what needs to be considered in order to protect cultural property, to point out what can be done, but also to provide guidelines for planning the prioritization of investments in the protection of cultural property. Due to the existence of modern techniques, some cultural goods can be "conserved" by digitizing or virtually moving them, but for a large part of cultural goods without timely planning and preventive activities, there may be a permanent loss of historical and cultural values.